Nanoparticle-Induced Augmentation of Neutrophils’ Phagocytosis of Bacteria - Rubey, Kathryn M.; Mukhitov, Alexander R.; Nong, Jia; Wu, Jichuan; Krymskaya, Vera P.; Myerson, Jacob W.; Worthen, G. Scott; Brenner, Jacob S. (Frontiers in Pharmacology, 2022)
Despite the power of antibiotics, bacterial infections remain a major killer, due to antibiotic resistance and hosts with dysregulated immune systems. We and others have been developing drug-loaded nanoparticles that home to the sites of infection and inflammation via engineered tropism for neutrophils, the first-responder leukocytes in bacterial infections. Here, we examined how a member of a broad class of neutrophil-tropic nanoparticles affects neutrophil behavior, specifically questioning whether the nanoparticles attenuate an important function, bacterial phagocytosis. We found these nanoparticles actually augment phagocytosis of non-opsonized bacteria, increasing it by ~50%. We showed this augmentation of phagocytosis is likely co-opting an evolved response, as opsonized bacteria also augment phagocytosis of non-opsonized bacteria. Enhancing phagocytosis of non-opsonized bacteria may prove particularly beneficial in two clinical situations: in hypocomplementemic patients (meaning low levels of the main bacterial opsonins, complement proteins, seen in conditions such as neonatal sepsis and liver failure) or for bacteria that are largely resistant to complement opsonization (e.g., Neisseria). Additionally, we observe that; a) prior treatment with bacteria augments neutrophil uptake of neutrophil-tropic nanoparticles; b) neutrophil-tropic nanoparticles colocalize with bacteria inside of neutrophils. The observation that neutrophil-tropic nanoparticles enhance neutrophil phagocytosis and localize with bacteria inside neutrophils suggests that these nanoparticles will serve as useful carriers for drugs to ameliorate bacterial diseases.